Comparison of therapy-related myelodysplastic syndrome with ring sideroblasts and de novo myelodysplastic syndrome with ring sideroblasts. (November 2019) - Chen, Zhining; Wang, Sa A.; Goswami, Maitrayee; Tang, Guilin; Routbort, Mark J.; Patel, Keyur P.; Luthra, Rajyalakshmi; Medeiros, L. Jeffrey; Ok, Chi Young
Highlights: TP53 mutations were more common, but SF3B1 mutations were less common in t-MDS-RS. Mutations in SF3B1, U2AF1, SRSF2 and ZRSR2 were less common in t-MDS-RS. Overall survival was poor in t-MDS-RS patients compared with de novo MDS-RS. Survival of patients with t-MDS-RS did not differ significantly from patients with t-MDS without RS. Abstract: Presence of RS is closely associated with SF3B1 mutation in de novo MDS. RS is also present in a subset of therapy-related MDS (t-MDS), but data is not available in t-MDS with RS (t-MDS-RS). Using NGS gene panel, we assessed t-MDS-RS (n = 38) and compared the result with d-MDS-RS (n = 174). Commonly mutated genes were TP53 (56.5%), TET2 (39.1%), SF3B1 (35.7%), ASXL1 (30.4%), DNMT3A (17.4%), RUNX1 (17.4%) and SRSF2 (14.3%). Compared with d-MDS-RS, TP53 mutation was more common but SF3B1 mutation was less common in t-MDS-RS (p < 0.05). In t-MDS-RS, Mutations in 4 genes ( SF3B1, U2AF1, SRSF2 and ZRSR2 ) involving the RNA splicing were found in about 50% of patients compared to ˜90% in d-MDS-RS. Overall survival was by far worse in t-MDS-RS compared to d-MDS-RS (median overall survival: 10.9 months and 111.9 months in t-MDS-RS and d-MDS-RS, respectively, p < 0.05). Progression to acute myeloid leukemia was more common in t-MDS-RS (18.4% vs. 7.4% in t-MDS-RS and d-MDS-RS, respectively, p < 0.05). Unlike de novo MDS, t-MDS-RS did not have different outcome compared to t-MDS without RS (median OS: 10.9 months vs. 14.3 months, respectively, p = 0.2341). Our data demonstrate that presence of RS is not associated with superior outcome in t-MDS. Mutation profiles suggest RS in t-MDS might be a secondary event in at least 50% of the cases or not related to mutations in RNA splicing machinery unlike d-MDS where mutations in RNA splicing machinery occur early and as associated with ineffective erythropoiesis.